「文化の翻訳」とイスラーム - 齋藤 剛 (通訳翻訳研究, 2025)
Since British social anthropologist Evans-Pritchard emphasized the significance of translation in 1950, the concept of ‘translation of cultures’ has emerged as a key metaphor underlying the scholarly work of anthropology, which aims to understand “other cultures”. However, from the 1970s to the 1980s, fundamental criticisms challenged anthropology’s core concepts such as society, culture, and nation; the relationship between colonialism and anthropology; and association between researchers and local inhabitants. Consequently, the concept of ‘translation of cultures’ also faced severe criticism and entered a period of retreat. Taking such criticism seriously, Japanese social anthropologist Kazuo Ohtsuka (1949–2009), whose work focused on the Middle East and Islam, attempted to reflect on the possibility of ‘translation of cultures’. The purpose of this article is to review Ohtsuka’s works to evaluate his theoretical contribution and scope of analyses on subjects such as (1) the probability of translating local terms into analytical expressions, (2) translating the cultural meanings of religious concepts and cultural items within socio-historical contexts, and (3) the circulation and consumption of translated universal and local concepts and their effects.